2014
DOI: 10.5586/asbp.1997.002
|View full text |Cite
|
Sign up to set email alerts
|

The ultrastructure of the mature embryo sac in the natural tetraploid of red clover (Trifolium pratense L.): that has a very low rate of seed formation

Abstract: In this study, ultrastructural organization of cells in the mature embryo sac of natural tetraploid Trifolium pratense L. was investigated. The mature embryo sac of this plant contains an egg cell with two synergids at the micropylar end, and a central cell with two polar nuclei. The ultrastructure of these cells agrees with what is known for most angiosperms studied with the electron microscope. The egg cell is a large and highly vacuolate cell, partially surrounded by a wall. Much of the cytoplasm i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…According to Garcia de Castro and Martinez-Honduvilla (1984) , seed ageing is a complex process, so it is essential to investigate this process at the subcellular level in order to understand the best conditions for seed storage. Despite the publication of numerous papers on seed ultrastructure at various phases of development during the last two decades ( Berjak et al 1994 ; Algan and Bakar 1997 ; Wang and Berjak 2000 ; Wiśniewska et al 2006 ; Teixeira and Machado 2008 ; Egorova et al 2010 ; Moura et al . 2010 ; Chan and Belmonte 2013 ; Hu et al 2013 ; and citations therein) knowledge of the ultrastructural changes that occur during seed storage is still insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…According to Garcia de Castro and Martinez-Honduvilla (1984) , seed ageing is a complex process, so it is essential to investigate this process at the subcellular level in order to understand the best conditions for seed storage. Despite the publication of numerous papers on seed ultrastructure at various phases of development during the last two decades ( Berjak et al 1994 ; Algan and Bakar 1997 ; Wang and Berjak 2000 ; Wiśniewska et al 2006 ; Teixeira and Machado 2008 ; Egorova et al 2010 ; Moura et al . 2010 ; Chan and Belmonte 2013 ; Hu et al 2013 ; and citations therein) knowledge of the ultrastructural changes that occur during seed storage is still insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…americanum) grown in Turkey are diploids; however, T. pratense L. collected by Elci (1982) for the first time in the Tortum district of Erzurum was found to be a natural tetraploid with low seed settings and hard seed problems. Algan and Bakar (1997) reported that degenerations in the embryo sac might affect the rate of seed settings as well as fertility failure. Hard and soft seed structure, germination, and regeneration of the plant parts were also studied previously (Colgecen et al, 2008).…”
Section: Introductionmentioning
confidence: 99%